Uji Kesetaraan Aktivitas Antioksidan Seduhan Bunga Kenop (Gomphrena globosa L.) dengan Vitamin C Menggunakan Metode DPPH - Rohmah, Martina Kurnia; Yulianti, Ella Rahman; Ambari, Yani (Bioma : Berkala Ilmiah Biologi, 2022)
Steeping of Kenop flower (Gomphrena globosa L.) is widely used as a health herbal drink that contains betacyanin and flavonoid compounds that act as antioxidants. This study aims to determine the equivalence of vitamin C levels in steeping of Kenop Flower (Gomphrena globosa L) using the DPPH method. The DPPH method is a simple, fast, inexpensive and can be used to measure the ability of an antioxidant. Data analysis of the absorbance of the steeping of the Kenop flower was calculated using TAC (Total Antioxidant Capacity Index). Phytochemical screening of infusion of the positive Kenop flower contains alkaloids, flavonoids, saponins, tannins and triterpenoids. Kenop flower is made with various concentrations of 5, 10 and 15 gr is steeping in 100 ml aquades. The antioxidant activity of steeping of Kenop flower 50, 100, and 150 mg/ml was equivalence with vitamin C respectively at 9,71 ppm (0,009 mg/ml) 13,96 ppm (0,013 mg/ml), and 15,18 ppm (0,015 mg/ml).